Leishmania amazonensis Engages CD36 to Drive Parasitophorous Vacuole Maturation - Okuda, Kendi (PLoS Pathog, 2016)
Leishmania amastigotes manipulate the activity of macrophages to favor their own success. However, very little is known about the role of innate recognition and signaling triggered by amastigotes in this host-parasite interaction. In this work we developed a new infection model in adult Drosophila to take advantage of its superior genetic resources to identify novel host factors limiting Leishmania amazonensis infection. The model is based on the capacity of macrophage-like cells, plasmatocytes, to phagocytose and control the proliferation of parasites injected into adult flies. Using this model, we screened a collection of RNAi-expressing flies for anti-Leishmania defense factors. Notably, we found three CD36-like scavenger receptors that were important for defending against Leishmania infection. Mechanistic studies in mouse macrophages showed that CD36 accumulates specifically at sites where the parasite contacts the parasitophorous vacuole membrane. Furthermore, CD36-deficient macrophages were defective in the formation of the large parasitophorous vacuole typical of L. amazonensis infection, a phenotype caused by inefficient fusion with late endosomes and/or lysosomes. These data identify an unprecedented role for CD36 in the biogenesis of the parasitophorous vacuole and further highlight the utility of Drosophila as a model system for dissecting innate immune responses to infection.